2015
DOI: 10.1186/s12864-015-1784-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity and differential expression of major phenylpropanoid-flavonoid biosynthetic genes among three mango varieties

Abstract: BackgroundMango fruits contain a broad spectrum of phenolic compounds which impart potential health benefits; their biosynthesis is catalysed by enzymes in the phenylpropanoid-flavonoid (PF) pathway. The aim of this study was to reveal the variability in genes involved in the PF pathway in three different mango varieties Mangifera indica L., a member of the family Anacardiaceae: Kensington Pride (KP), Irwin (IW) and Nam Doc Mai (NDM) and to determine associations with gene expression and mango flavonoid profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Due to nutritional and commercial values of phenolics, the biosynthetic pathway of phenolics has been investigated [18], which suggested gene expression profiles affected phenolics accumulation. The up-regulation of phenylalanine lyase ( PAL ) and chalcone synthase ( CHS ) in up-stream biosynthesis pathways lead to a high accumulation of phenolics in mango peel, and similar patterns have also been reported in tomato [19]. Isoflavone synthase (IFS) is the first catalyzing enzyme in the isoflavone biosynthesis pathway, which leads to the production of isoflavones in legumes [20].…”
Section: Introductionmentioning
confidence: 97%
“…Due to nutritional and commercial values of phenolics, the biosynthetic pathway of phenolics has been investigated [18], which suggested gene expression profiles affected phenolics accumulation. The up-regulation of phenylalanine lyase ( PAL ) and chalcone synthase ( CHS ) in up-stream biosynthesis pathways lead to a high accumulation of phenolics in mango peel, and similar patterns have also been reported in tomato [19]. Isoflavone synthase (IFS) is the first catalyzing enzyme in the isoflavone biosynthesis pathway, which leads to the production of isoflavones in legumes [20].…”
Section: Introductionmentioning
confidence: 97%
“…A previous study has revealed that the upstream genes have been observed to evolve slower than downstream genes in the secondary metabolite biosynthesis [86]. A similar pattern has been observed in mango with a high number of variations in the downstream genes of the flavonoid biosynthetic pathway [87]. This finding suggests that mutations in the flavonoid biosynthetic genes could affect the accumulation of secondary metabolite end products such as anthocyanin and proanthocyanidin.…”
Section: Resultsmentioning
confidence: 53%
“…In comparison to the number of SNPs in the structural genes, fewer SNPs were found in the transcription factor, and this finding suggests that the character of the transcription factors are highly conserved compared to other classes of genes [89]. In conclusion, polymorphism in the transcription factor plays a crucial role in the biosynthetic pathway as it is responsible for regulating the functions of biosynthetic genes and affecting the production of secondary metabolites [86, 87].…”
Section: Resultsmentioning
confidence: 99%
“…All primers were obtained from Elisabeth Pharmacon. Sequences of all primers are introduced in Table 3 [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. All PCR reactions were performed in 25 µL of the total volume.…”
Section: Methodsmentioning
confidence: 99%
“…Each reaction mixture contained 9.5 μL of PCR water, 12.5 µL of SYTO9 MasterMix, 1 μL of each primer (solutions diluted to 10 pmol/µL), and 1 μL of template DNA of concentrations shown in Table 3 . Cycling profiles for each pair of primers are introduced in Table 3 , too [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The reason for using undiluted DNA isolates as opposed to adjusting the concentration of all DNA isolates to the same value was the fact that the different dilutions would also influence the concentration of contaminants in the DNA isolates, which could in turn influence the results.…”
Section: Methodsmentioning
confidence: 99%